2014
DOI: 10.1142/s1793292014500994
|View full text |Cite
|
Sign up to set email alerts
|

Light-Sensitive Silicon Nanowire Array Field Effect Transistor for Glucose Detection

Abstract: We report on the sensitive detection of glucose using silicon nanowire array field-effect-transistor ( SiNW -FET) upon illumination. The uniformly distributed and size-controlled SiNWs were fabricated by "top-down" approach. The fabricated SiNW -FET device was evaluated for detection of glucose in the range of 100–900 mg/dL. The SiNW -FET shows enhanced sensitivity of 0.988 ± 0.030 nA (mg/dl)-1 upon illumination at 480 nm light as compared to without illumination as 0.486 ± 0.014 nA (mg/dL)-1. The presented Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The robust behaviors in silicon nanowires (SiNWs) material properties, such as high mechanical strength, 1 stability in thermal, 2 chemical 3 and biological 4 environments, unique thermoelectric performances, 5 enriched optical and electronic 6,7 behaviors pave the way for research as well as industrial pursuits. The unique sp 3 -bonded crystal structure and the low work function of SiNWs show it to be a potential candidate to be employed as a cold cathode material for¯eld emission device applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The robust behaviors in silicon nanowires (SiNWs) material properties, such as high mechanical strength, 1 stability in thermal, 2 chemical 3 and biological 4 environments, unique thermoelectric performances, 5 enriched optical and electronic 6,7 behaviors pave the way for research as well as industrial pursuits. The unique sp 3 -bonded crystal structure and the low work function of SiNWs show it to be a potential candidate to be employed as a cold cathode material for¯eld emission device applications.…”
Section: Introductionmentioning
confidence: 99%
“…The unique sp 3 -bonded crystal structure and the low work function of SiNWs show it to be a potential candidate to be employed as a cold cathode material for¯eld emission device applications. 7,8 Over past few years, many other nanomaterials, such as aligned carbon nanotubes, 10 ultra-nanocrystalline diamond lms, [11][12][13] arrays of gallium nitride nanorods, 14 titanium dioxide nanotubes, 15 cone-shaped zinc oxide nanostructures, 16 tin oxide nanotubes 17 and needle-shaped molybdenum trioxide 18 are showing much more e±ciency in¯eld emission with very low turn-on¯eld. Moreover ion implantation, 19 metallic coating 20 and H 2 surface treatment on diamond lms 21 are observed to signi¯cantly enhance the electron¯eld emission (EFE) properties.…”
Section: Introductionmentioning
confidence: 99%
“…The two nanomaterials of most concern today are silicon (Silicon nanowires-SINW) 114 and carbon (graphene and carbon nanotubes-CNTS). 115 SINW has proven to be highly sensitive for unlabeled and real-time inspection, but also has potential commercial potential due to its feasibility in mass production in the semiconductor industry.…”
Section: Glucose Monitoring Sensormentioning
confidence: 99%
“…Unfortunately, SiNW-FET is limited to the detection of analytes with a certain charge, and the specific detection of weakly charged or uncharged analytes remains a challenge [ 16 ]. It has been reported that the method of modifying glucose oxidase on the surface of SiNW-FET biosensors has been successfully used to measure uncharged low-molecular-weight molecular glucose with detection limits down to μM levels [ 17 , 18 ]. In addition, the limitation of low charge analytes is difficult to detect.…”
Section: Introductionmentioning
confidence: 99%